Manajemen Jalan Nafas Pada Pasien Asma Bronkial dengan Pola Nafas Tidak Efektif di Rumah Sakit Umum Daerah Tais Kabupaten Seluma - Wira Fitriani; Anditha Ratnadhiyani (Journal of Innovative and Creativity, 2026)
Bronchial asthma is a chronic respiratory disease characterized by airway narrowing, increased mucus production, and bronchial hypersensitivity, which may lead to ineffective breathing patterns. This condition requires appropriate nursing management to maintain airway patency and improve pulmonary ventilation. This case study aimed to describe the implementation of airway management nursing care in patients with bronchial asthma experiencing ineffective breathing patterns at RSUD Tais, Seluma Regency. The study employed a qualitative descriptive design using a nursing process approach involving two patients with bronchial asthma during exacerbation. Nursing interventions were carried out for three days and included semi-Fowler positioning, Pursed Lip Breathing exercises, Buteyko breathing technique, and steam inhalation therapy with eucalyptus oil. Data were collected through interviews, observation, and physical examination and were analyzed using descriptive narrative methods. The evaluation results showed improvements in both patients, including reduced dyspnea, improved respiratory rate and depth, increased oxygen saturation, and decreased adventitious breath sounds. Asthma control scores improved from uncontrolled to fully controlled categories. In conclusion, the implementation of Evidence-Based Nursing airway management is effective in improving breathing patterns and oxygenation status in patients with bronchial asthma. These interventions are recommended as part of standard nursing care for patients with bronchial asthma experiencing breathing pattern disturbances.